2010
DOI: 10.1016/j.accfor.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of an early stage R&D-intensive firm under financialization

Abstract: Original article can be found at: http://www.sciencedirect.com/science/journal/01559982 Copyright Elsevier Ltd.The financialization literature considers the impact of financial markets on corporate strategy, governance, financial performance and the distribution of resources between various stakeholder groups. Capital market demands modify strategic priorities, governance and managerial narratives about performance because this helps justify value creation and value absorption in an era of shareholder value. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Presently, business context forces firms, particularly small-and medium-sized enterprises (SMEs), to be innovative, review their methods regularly, adjust their strategy to their changing environment (Ates et al, 2013) and keep a close eye on their performance (Raymond et al, 2009;Cocca and Alberti, 2010). However, research has shown that SMEs often find it difficult to implement a performance measurement and management systems (PMMSs) due to their inherent characteristics, such as their limited human and financial resources, the absence of formal organizational structures and strategies and the dominance of intuition in decision-making (Gleadle and Haslam, 2010;Hudson et al, 2001;King et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, business context forces firms, particularly small-and medium-sized enterprises (SMEs), to be innovative, review their methods regularly, adjust their strategy to their changing environment (Ates et al, 2013) and keep a close eye on their performance (Raymond et al, 2009;Cocca and Alberti, 2010). However, research has shown that SMEs often find it difficult to implement a performance measurement and management systems (PMMSs) due to their inherent characteristics, such as their limited human and financial resources, the absence of formal organizational structures and strategies and the dominance of intuition in decision-making (Gleadle and Haslam, 2010;Hudson et al, 2001;King et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, the national level is central to Belfrage's (2008) analysis of how states manage new pension systems. Furthermore, financialisation has been studied and connected to internal corporate strategies and management orientation (Andersson et al, 2010;Gleadle and Haslam, 2010;Lazonick and O'Sullivan, 2000). In addition, the individual level has been central in studies of how individuals manage and are affected by their private investments, pensions, mortgages, and credit card expenditures, etc.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The finance literature considers the impact of capital markets on the company's financial performance and the distribution of resources among different stakeholders [12]. In an efficient market, where information is quickly evaluated and reflected in the market prices, companies use many possibilities to finance their operations, among which include the issuing of shares.…”
Section: Research Hypothesesmentioning
confidence: 99%